A system of Indian logic : the Nyāya theory of inference : analysis, text, translation and interpretaion of the anumāna section of Kārikāvalī, Muktāvali and Dinakarī /: the Nyāya theory of inference : analysis, text, translation and interpretaion of the anumāna section of Kārikāvalī, Muktāvali and Dinakarī. (2013) - Unknown
No abstract available